Utilization of Fruit Peel Waste Left From Ceremonials Into Economical Value Products in Batuan Village, Sukawati, Gianyar, Bali - Muliarta, I Nengah; Setianingsih, Ni Luh Putu Putri; Sadguna, Dewa Nyoman; Putra, I Ketut Suwarmadi; Dusak, Putu Gede Bayu Janardhana; Mertayasa, Komang Gede (Asian Journal of Community Services, 2024)
Several types of fruit that support ecotourism in the application of food waste include banana peels, apple peels, dragon fruit peels, and manga peels, which will be made into chips and tea products using good hygiene and quality standards. Innovative problem-solving and technology have emerged as promising approaches. The target partners are housewives who are members of the PKK in Batuan Village, Sukawati, from underdeveloped neighborhoods with a great desire to start their own businesses but who are not yet economically productivefrom underdeveloped neighborhoods with a great desire to start their own businesses but who are not yet economically productive. The methods that will be used are interviews, face-to-face, counseling, and direct practice. The output target to be achieved is that the training participants are independently able to make fruit skin chips and tea products from fruit skins so that they can become economically independent